Hormone levels in the outer layer of domestic goose (Anser anser domesticus) eggs change over the laying season. (1st August 2013) - Kent, John; Murphy, Kenneth; Salamon, Attila; Hayden, Thomas; Möstl, Erich
In general, avian species produce clutches of more than one egg. Differential investment in egg weight and hormone levels is possible and their effects on development and behaviour can be measured. Here we investigated changes in three hormones (testosterone, T; androstenedione, A4 and progesterone, P4) in the outer layer of yolks of infertile domestic goose eggs over the course of a laying season. There was a significant change in the concentration of all three hormones: T and P4 increased in a linear manner across the season whilst A4 increased until mid season and then steadily decreased. The correlation between T and P4 (r = 0.613, P<0.001), and between T and A4 (r = 0.746, P<0.001) were both positive, but the relationship between A4 and P4, while positive was not strong (r = 0.379, P<0.001), although still significant. The increase in P4 over the laying season is consistent with the transition from a laying to a broody state. The increase in T is consistent with a trade-off for the seasonal decline in egg weight.